Pengaruh Harga terhadap Keputusan Pembelian Kain Tenun Ikat Sikka - Siti Suhartanti; Nur Chotimah; Muhammad Syahrun (Journal Economic Excellence Ibnu Sina, 2025)
Ikat weaving is one of the typical cultural heritage of East Nusa Tenggara, especially the Sikka area in Maumere. This traditional fabric is made through a process of weaving manually by the local community, making it unique and has high artistic value. Even though it is in the modern era, the appeal of ikat woven fabrics remains strong and has not been displaced by the development of the times. The production of this fabric is still actively ongoing and has become a symbol of regional cultural identity that is full of philosophical and aesthetic meaning. This study aims to analyze the influence of price on the purchase decision of Sikka ikat woven fabric by consumers. The research was carried out at the Alok Maumere Market in 2021 with a sample of 96 respondents, who were selected using random sampling techniques. The research method used is quantitative descriptive, with validity, reliability, normality, linearity, and heteroscedasticity testing. The result of the simple linear regression analysis shows an equation: purchase result = 17.140 + 0.603 price. The value of t is calculated (7.993) > t of the table (1.985), so that H₀ is subtracted and H₁ is accepted. This means that price has a significant effect on purchasing decisions. The coefficient of determination (R² = 0.398) shows that price explains 39.8% of the variation in the purchase decision. Thus, it can be concluded that price has a positive influence on consumers' decisions in buying Sikka ikat woven fabrics. This means that the more the price is in line with consumer expectations, the higher the buying interest in this traditional product. This research provides important input for MSME actors and local artisans to be more careful in determining competitive prices while still reflecting the quality and cultural value of the product.